DETERMINAÇÃO DAS PROPRIEDADES MECÂNICAS E CARACTERIZAÇÃO DE FILME FINO PRODUZIDO POR IMPREGNAÇÃO FORÇADA - Sequinel, Thiago (2008)
In this work has been developed a new way to impregnate using high pressure. Thin film were obtained in soda-lime glass surface when it were used Co3O4, Al2O3, TiO2 and SnO2 as a oxides deposited, across a furnace confectioned for this experiment. SnO2 was results of two different chemical methods of synthesis. It was able to control tree variable: temperature, time and final pressure of test from an initial pressure of dry synthetic air. Results were characterized by X-ray diffraction, X-ray fluorescence of the powder and film morphology was analyzed by scan electronic microscopy. Using nanoindentation with Berkovich tip the mechanical properties were determined of the films produced, calculating the Young Modulus and hardness, and using Vickers indentation was possible to calculate the fracture toughness. Experimental process results to different oxides were compared among them and it were able to verify the viability of this new way to product a thin film.